PENGARUH PERSON ORGANIZATION FIT (PO-FIT) DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Siti Fatimah; Nurbaiti Nurbaiti; Rahmat Daim Harahap (Commodity : Jurnal Perbankan dan Keuangan Islam, 2023)
This study was to determine the effect of Person Organization Fit (PO-Fit) and Work Environment on Employee Performance with Organizational Commitment as an Intervening variable. This study uses a quantitative method with a path analysis approach. Data collection techniques through questionnaires distributed to employees of PT. Bank Sumut Medan Sharia Branch Office Brigjend Katamso with a sample of 33 respondents used a saturated sampling technique. This analysis includes instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing and path analysis with the SPSS version 22 program. The results show (1) Person Organization Fit (POFit) has a significant effect on Employee Performance, (2) Environment Work has a significant effect on Employee Performance, (3) Person Organization Fit (PO-Fit) has a significant effect on Organizational Commitment, (4) Work Environment has a significant effect on Organizational Commitment, (5) Organizational Commitment has no significant effect on Employee Performance, (6) Person Organization Fit (PO-Fit) has no direct effect on Employee Performance through Organizational Commitment as an Intervening variable, (7) Work Environment has no direct effect on Employee Performance through Organizational Commitment as an Intervening variable, (8) Person Organization Fit (PO- Fit), Work Environment and Organizational Commitment simultaneously influence Employee Performance